Ovitrap Modification in Improving the Ability of Aedes Sp. Egg Trapping in Banjarbaru City - Tien Zubaidah; Erminawati Erminawati; Muhamad Ratodi (Universitas Airlangga, 2020)
Introduction: Dengue Hemorrhagic Fever (DHF) is a vector-borne disease that spreads through the bite of Aedes aegypti and Aedes albopictus. Until recently, vector control still becomes an essential step in breaking the dengue transmission chain. Besides of imago or larvicide method, the ovitrap way is also often used to trap the eggs of Aedes sp. This study aims to determine the trapping ability of modified ovitrap with various container colors and shrimp-paste attractant concentration levels. Method: This study was an experimental study using a post-test only design. This Research's object was Aedes sp eggs trapped in modified ovitrap at 20 research locations in Banjarbaru City. The data obtained were analyzed statistically using the Kruskal Wallis test. The Research used The Mann-Whitney test to perform a post-hoc analysis. Result and Discussion: Results have shown that differences in attractant concentration and color of ovitrap have a significant effect in attracting Aedes sp to lay eggs. Zero percent concentration (without attractants) has a substantial difference in trapping Aedes sp with 10, 20, and 30% concentrations. Colorless ovitrap is also significantly different from black and green ones in trapping Aedes sp eggs. Conclusion: The use of attractants with a 10% shrimp-paste concentration solution and a black ovitrap can be an alternative to control DHF vectors affordable and safer for the environment and humans.